EFEKTIVITAS WAKTU APLIKASI DAN DOSIS MIKORIZA PADA PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays L. SACCHARATA) - Widyana Rahmatika; Sisilia Kharomah (Universitas Tribhuwana Tunggadewi, 2021)
This study aimed was to determine the appropriate application time and dose of mycorrhizae for the growth and yield of sweet corn (Zea mays L.). This study used a Randomized Block Design (RAK) using two factors with three treatments. The first treatment was application time, M1= 3 days before planting, M2= 6 days before planting, M3= 9 days before planting. The second treatment was mycorrhizal fertilizer, N1 = 1.8 kg/ha, N2 = 3.6 kg/ha, N3 = 5.4 kg/ha and N4 = 7.2 kg/ha . The results showed that the interaction only occurred in plant height parameters 28 days after planting. Furthermore, the number of leaves, stem diameter, cob weight without husk only showed significant results in the single factor mycorrhizal dose treatment, with the best treatment being in the mycorrhizal fertilizer 5.4 kg/ha treatment.